Parliament of things and enactment of third entities: object-subject/subject-object encounters from cuban urban gardens to United States' robotic labs. - Saramifar, Younes; Plonska, Ola; Kootstra, Jochem (Journal for Cultural Research, 2018)
Things/objects/materials/nonhumans are integral components of everyday material ecology of humans. The nonhuman elements contribute to sociality, socialization and configuration of political subjectivities. We explore the dynamics of subject-object relationships via ethnographies of urban gardens and robotic labs. We trace the dynamics of man-plant relationships in urban gardens of Cuba and engineer-humanoid relationships in the United States to highlight how these relationships inform the politics and ethical complexity of human-centred ecologies. This collaborative effort offers two different case studies to broaden the notions of materiality while critiquing the relationality bound between subjects and objects instead of exploring the emergent properties of their relationship. Our ethnographies are a form of hands-on anthropology that outlines the third entity that emerges from the subject-object relationship and configures the material ecology of everyday lives. Our discussion contributes to the complexities of politics of everyday life and to the challenges of our contemporary era by highlighting the importance of details of everyday lives and how we craft relationships with nonhuman people.